UNSUR PAKSAAN YANG TERKANDUNG DI DALAM SEBUAH PERJANJIAN SEBAGAI ALASAN PEMBATALAN PERJANJIAN (STUDI KASUS : PUTUSAN MAHKAMAH AGUNG NO. 943 K/PDT/2012) - MARANATHA MONICA JUSTICIA DOLOKSARIBU (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:1. Runtung 2. Muhd Yamin 3. T. Keizerina Devi A One of the essential requirements for the validity of a contract is the agreement between the parties concerned. In the civil case, the requirement is grouped as the subjective requirement. No one knows whether there is duress in a contract in signing it without any complaint from a harmed party. In-depth research was conducted to find out a normative standard which stated that there was duress in a civil case which was caused by duress in a contract while the judge did not find it, and judge’s consideration in stating that there was duress for cancelling the contract in the Ruling of the Supreme Court no. 943 K/PDT/2012. The research used judicial normative and descriptive analytic methods. The data consisted of primary and secondary data. Primary data were obtained from judges’ verdicts, while secondary data were obtained from primary, secondary, and tertiary legal materials. They were all gathered by conducting documentary study and analyzed qualitatively. The result of the research shows that normatively duress in the civil case can cancel a contract as stipulated in Article 1324 of the Civil Code which states that as contract can be cancelled when duress is done toward the third party as it is regulated in Article 1323 of the Civil Code. It can also be cancelled when the duress is done toward a married couple or their families toward their upper or lower line of as it is stipulated in Article 1326 of the Civil Code which states that “…feelings of fear which is caused by respect toward father, mother, or other family members in the upper line, without being accompanied by duress, cannot cancel an agreement.” The Ruling of the Supreme Court No. 943 K/PDT/ 2012 has been in line with the legal provisions that a Notary’s duty is to compare the relationship between legal provisions and the stakeholders in a written form and in certain form so that an authentic deed becomes strong evidence in the legal process of formal and material case whether they are accepted in the hearing as an authentic evidence before the judge in giving his verdict about the truth of a certain case. Keywords: Cancellation of a Contract, Duress, House of Detention